Pengaruh Kemandirian Keuangan Daerah, Diferensiasi Fungsional Dan Spesialisasi Fungsional Terhadap Tingkat Pengungkapan Wajib Laporan Keuangan Pemerintah Daerah - Suparno Suparno; Riska Nanda (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this study was to examine the effect of local financial independence , functional differentiation and functional specialization of the level of mandatory disclosure of financial statements of local government . The average level of mandatory disclosure of the financial statements of local government in regencies/ cities in Aceh amounted to 48.65 % . The data used are secondary data from the financial statements of the second level governments . Total population in this study were 23 regencies/ cities in Aceh 2013-2014 fiscal year . Statistical method used to test the hypothesis is multiple linear regression . The results showed that, simultaneously local financial independence, functional differentiation and functional specialization affect the level of mandatory disclosure of financial statements of local government. Partially local financial independence affects the level of mandatory disclosure of financial statements of local government, functional differentiation affects the level of mandatory disclosure of financial statements of local government, and functional specialization affect the level of mandatory disclosure of financial statements of local government.